О задаче без начальных условий для одной нелинейной вырождающейся параболической системы - Пукач, П.Я. (Український математичний журнал, 1994)
Вказано деякі класи існування та єдиності розв'язку задачі без початкових умов для однієї нелінійної параболічної системи, що вироджується. Одержано умови єдиності при наявності та відсутності обмежень на поведінку розв'язку при t→−∞. Існування доведено при довільній поведінці при t→−∞ правої частини системи. Some classes are indicated, for which a solution of a problem without initial conditions for a certain nonlinear degenerating parabolic system exists and is unique. The uniqueness conditions are established both in the case where restrictions are imposed on the behavior of the solutions as t→−∞ and in the case where they are not imposed. The existence is proved for an arbitrary behavior of the right-hand side of the system as t→−∞